Catalytic cyclohexane oxidation in the presence of alcohols of different nature - Супрун, Олександр Олександрович; Реутський, Віктор Володимирович; Іващук, Олександр Сергійович; Мудрий, Сергій Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
One of the ways of improving homogeneous catalytic oxidation of cyclohexane is the use of additives to industrial catalysts based on metals of variable valency. The analysis of literature sources has shown that alcohols that are formed in the process of oxidation and are able to form intermediate complexes with a catalyst have a significant impact. The effect of C2-C5 alcohol additives on the process of homogeneous catalytic oxidation of cyclohexane was studied in the paper. In the paper, the oxidation indices using binary catalytic systems of cobalt naphthenate – alcohol are given. The qualitative and quantitative effect of additives of monohydric and polyhydric alcohols on the process was defined, and their effects were compared. The dependences of the reaction rate on the nature of additives and the ratio between the components were determined. The optimal binary catalytic systems for the liquid-phase homogeneous catalytic oxidation of cyclohexane were selected, the use of which will allow improving the technical and economic production indices.